Framing Gaming: The Effects of Media Frames on Perceptions of Game(r)s. (November 2016) - Kümpel, Anna Sophie; Haas, Alexander
This study investigates the effects of media frames on attitudes toward video games, perceptions of their users, and consequences. Prior research has shown that gaming is a controversial issue, with media coverage focusing on either risks or opportunities. To examine the effects of these portrayals, the present study used a 2 × 2 experimental design and exposed participants ( N = 360) to a news article that framed gaming in terms of risk or opportunity on the journalistic level and on the level of a corresponding expert statement. By examining the perceived negative effects of games, this study extends previous research by combining framing and third-person research. Results showed that framing gaming indeed had an effect on participants' attitudes. This framing effect was moderated by individual video game use. Despite identifying a traditional third-person perception regarding negative video game effects, we found framing to have no significant influence on third-person perceptions.